PENGARUH FINANCIAL SELF EFFICACY, LITERASI KEUANGAN, DAN INKLUSI KEUANGAN TERHADAP PENGELOLAAN KEUANGAN PADA ANGGOTA PKK KECAMATAN PANTI - Wati Cantika Putri, Ayuni Alda; Supeni, Retno Endah; Setianingsih, Wahyu Eko (Relawan Jurnal Indonesia, 2025)
Family financial management is an important aspect in efforts to improve economic welfare, especially for PKK mothers who act as the main managers of family finances. This study aims to analyze the effect of financial self-efficacy, financial literacy, and financial inclusion on financial management in PKK members of Panti District. This study used a quantitative method with a survey approach and data collection was carried out through questionnaires distributed to 181 PKK members of Panti District online and face-to-face. The results showed that financial self-efficacy partially had the most significant effect on financial management, while financial literacy and financial inclusion partially had a significant effect on financial management. This finding confirms the importance of increasing these three variables in an effort to empower PKK mothers to be able to manage family finances more effectively, efficiently and wisely, so as to improve the economic welfare of families and communities in a sustainable manner.